Novel ultralow positioning of the umbilical artery catheter: A prospective pilot study - Tomaszkiewicz Anna; Szymański Piotr; Kruczek Piotr (Journal of Ultrasonography)
Thrombosis is a common complication of umbilical artery catheterization. The purpose of this study was to compare the novel ultralow umbilical artery catheter position (catheter tip at the junction of the umbilical and internal iliac arteries) versus the conventional high umbilical artery catheter position (tip in the aorta, above the diaphragm) for the incidence of thrombosis.